2009
DOI: 10.1227/01.neu.0000335648.31874.37
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Symptomatic Middle Cerebral Artery Stenosis With Balloon-Mounted Stents

Abstract: Primary stenting of symptomatic middle cerebral artery stenosis can be performed with high success and low complication rates. Randomized clinical studies are warranted to compare the safety and efficacy of various endovascular revascularization techniques with maximal medical therapy in patients with symptomatic intracranial atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
2
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 29 publications
6
35
2
1
Order By: Relevance
“…In this study, the 30-day rate of stroke or death in the PTAS group (2.8%) is substantially lower than the rates recently reported with the use of the Wingspan stent in SAMMPRIS trial (14.7%) 15 and also lower than previously reported in 2 Wingspan registries (rates ranging from 4.4% to 9.6%). 6,24,25 Additionally, in this study, all PTAS procedures were successfully performed, and the periprocedural complication rate was 0, which is better than Miao's retrospective study (5.3%) 14 and US multicenter experience (6.1%). 25 A recent systematic review demonstrated that the technical success rate for intracranial high grade stenosis ranges from 90% to 100%, 16 and the periprocedural complication rate ranges from 9.9% to 30%.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…In this study, the 30-day rate of stroke or death in the PTAS group (2.8%) is substantially lower than the rates recently reported with the use of the Wingspan stent in SAMMPRIS trial (14.7%) 15 and also lower than previously reported in 2 Wingspan registries (rates ranging from 4.4% to 9.6%). 6,24,25 Additionally, in this study, all PTAS procedures were successfully performed, and the periprocedural complication rate was 0, which is better than Miao's retrospective study (5.3%) 14 and US multicenter experience (6.1%). 25 A recent systematic review demonstrated that the technical success rate for intracranial high grade stenosis ranges from 90% to 100%, 16 and the periprocedural complication rate ranges from 9.9% to 30%.…”
Section: Discussionmentioning
confidence: 58%
“…In patients with good access, the placement of balloon-mounted stent is technically simpler and requires less procedural time. Although the MCA is more difficult to access than other intracranial arteries, 14 with training and careful selection of patients, a high success rate and low periprocedural complication rate can be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, a large single-center study of 113 patients treated with balloonmounted stents demonstrated stroke or transient ischemic attack in 6.74% and a restenosis rate of 20% during the follow-up period of 29Ϯ16 months. 13 Diabetes and hyperlipidemia were associated with the incidence of restenosis. As we await the results of the randomized, multicenter National Institutes of Health (NIH)-funded trial on the use of the Wingspan stent (Boston Scientific) for the treatment of ICAD (stenting versus aggressive medical management for preventing recurrent stroke in intracranial stenosis) and the VISSIT trial (Vitesse Intracranial Stent Study for Ischemic Therapy, Micrus Endovascular, see illustrative case in the Figure), we have a systematic review pooled data from of 31 studies (1177 procedures) using angioplasty and stenting for treatment of symptomatic, high-grade intracranial artery stenosis.…”
Section: Intracranial Artery Angioplasty and Stentingmentioning
confidence: 99%